2015
DOI: 10.1016/j.jcma.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic hematoma evacuation in patients with spontaneous supratentorial intracerebral hemorrhage

Abstract: With the introduction of the minimally invasive techniques and the evolution of the neuroendoscope and hemostatic agents, the median operative time and blood loss have been significantly decreased. Although the hematoma evacuation rates were similar between the endoscope (90%) and craniotomy (85%) groups, the median intensive care unit stay was decreased from 11 days to 6 days due to reduced surgical invasiveness. This represents an important advancement in treating spontaneous supratentorial ICH, and provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 18 publications
2
46
1
1
Order By: Relevance
“…Surgical evacuation of the intracerebral hematoma can reduce the hematoma mass, decrease ICP, improve regional blood flow, and restrict the release of toxic breakdown products by blood clot. Endoscopic surgery has been gaining popularity as a method for surgical intervention in ICH patients [15][16][17]. During the surgery, a transparent tube was inserted into the hematoma center, hematoma was evacuated by suction through the working space, and as the sheath was gradually withdrawn, the residual hematoma was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical evacuation of the intracerebral hematoma can reduce the hematoma mass, decrease ICP, improve regional blood flow, and restrict the release of toxic breakdown products by blood clot. Endoscopic surgery has been gaining popularity as a method for surgical intervention in ICH patients [15][16][17]. During the surgery, a transparent tube was inserted into the hematoma center, hematoma was evacuated by suction through the working space, and as the sheath was gradually withdrawn, the residual hematoma was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic surgery has been applied for the treatment of HICH in recent years. Many studies suggested that endoscopic evacuation showed efficacy and safety benefit for HICH patients (Cho, Chen, Chang, Lee, & Tso, ; Nagasaka et al, ), when compared with traditional craniotomy (Wang et al, ; Yamashiro, Hitoshi, Yoshida, & Kuratsu, ). The result is in accordance with the latest systemic review (Xia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a 2015 study, neuroendoscopic surgery was successfully performed in local anesthesia, 31 making it safer and feasible for older adults with cardiopulmonary morbidities. Our study also showed that neuroendoscopic surgery exhibited similarly high hematoma ER and low rebleeding rate compared with craniotomy, and it could shorten the surgical time greatly and thus reduce perioperative morbidity.…”
Section: Discussionmentioning
confidence: 99%